PREVENTING ROLLOVER PHENOMENON WITH AN ACTIVE ANTI-ROLL BAR SYSTEM USING ELECTRO-HYDRAULIC ACTUATORS: A FULL CAR MODEL - Van Tan, Vu (Journal of Applied Engineering Science, 2021)
This paper discusses the role of the active anti-roll bar system in order to enhance the roll stability of cars, thereby preventing rollover phenomenon in high speed emergency situations. First, an integrated full car model is proposed including the longitudinal, lateral, vertical motions and an electro-hydraulic actuator model. In this full car model, the control signal being the input current which is supplied to the actuators to create the active torques to improve the car's stability. This is the most general model in theory to study this active roll control system and is a big step forward compared to previous related studies. The optimal LQR control method has then been used to synthesize the controller based on the integrated model with 26 degrees of freedom. The criteria used to assess the vehicle roll stability are the sprung mass roll angle and the interactive force between the wheels and the road surface. The simulation results in the frequency domain and the validation in the time domain through the CarSim software's nonlinear car model clearly show the advantages of this active system with an optimal LQR controller in preventing vehicle rollover.
Keywords: active anti-roll bar system; electro-hydraulic actuator; roll stability; optimal control; linear quadratic regulator controller